A Study on the Effect of Neurogenesis and Regulation of GSK3β/PP2A Expression in Acupuncture Treatment of Neural Functional Damage Caused by Focal Ischemia in MCAO Rats. (10th July 2014) - Luo, Ding; Fan, Xiaonong; Ma, Congcong; Fan, Tongtao; Wang, Xiaoguang; Chang, Nvzi; Li, Lingxin; Zhang, Yanan; Meng, Zhihong; Wang, Shu; Shi, Xuemin
Abstract : 170 SD rats were randomly divided to five groups. Rats in model group, no-acupuncture group, and acupuncture group were subjected to MCAO surgery. Acupuncture group received 3 consecutive acupuncture treatments at a parameter that deep in 2 mm towards apex nasi and thrust/lifted at 3 times per second for 1 minute, while model group and no-acupuncture group were no-intervention control groups. Serious neural functional damage and sharp decrease of cerebral blood flow, obvious infarction volume, increased nestin mRNA expression, and immunopositive cells population (nestin +, BrdU + and nestin/BrdU + ) were found in MCAO rats which had not been observed in normal group and sham-operated group. However, the damage was attenuated by rat's "self-healing" capacity 3 days after MCAO. And the "self-healing" capacity can be strengthen by acupuncture treatment through increasing cerebral blood flow, neurogenesis, and regulation of gene transcription or GSK-3 β and PP2A expression. In conclusion, the present study indicates that the underlying mechanism of acupuncture treatment on neural functional damage caused by focal ischemia injury is a multiple interaction which may involve improved cerebral blood supply, neurogenesis, and regulation of gene transcription or GSK-3 β and PP2A expression in MCAO rats.